Silver-containing composite membranes comprising a layer of titanium silicalite, methods for their preparation and use in the synthesis of hydrogen peroxide
Patent Information
- Application Number
- CN202210841781.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-18
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-07-18
AI Technical Summary
然而该体系却存在钯膜低温溶氢后易氢脆破裂, H2O2在钯膜表面易氢化分解的问题
[0012] Through the above technical solution, this invention prepares a composite palladium-based alloy material with a face-centered cubic close-packed crystal structure using electroplating, and synthesizes titanium-silicon molecular sieves on the surface of the composite palladium-based alloy material using an in-situ hydrothermal method. On the one hand, this allows hydrogen and oxygen to be introduced into the reaction system from opposite sides of the membrane, achieving physical isolation between the combustible gas (H2) and the combustion accelerant (O2), ensuring the safety of the reaction. On the other hand, it enables the efficient synthesis of H2O2 at the composite membrane interface, greatly improving the H2O2 generation rate and purity, yielding high-quality electronic-grade H2O2, and reducing the pressure of subsequent product separation and purification. This invention does not require any external energy source; it uses the composite membrane material as a catalyst to directly synthesize H2O2 from hydrogen and oxygen, offering advantages such as a simple process, clean and environmentally friendly operation, long service life, and low energy consumption. Simultaneously, the composite membrane of this invention solves the problems of palladium membranes being prone to hydrogen embrittlement and cracking at low temperatures, resulting in reduced mechanical strength, and the problem of H2O2 easily decomposing on the palladium membrane surface, causing reduced H2O2 selectivity.
Smart Images

Figure CN117443211B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen peroxide preparation, specifically to a silver-containing composite membrane including a titanium-silicon molecular sieve layer, its preparation method, and its application in the synthesis of hydrogen peroxide. Background Technology
[0002] With the rapid development of the electronics and semiconductor industries, the demand for high-purity electronic-grade hydrogen peroxide (H2O2) used for silicon wafer cleaning and photoresist stripping is increasing daily. In my country, the anthraquinone method, which accounts for 99% of total H2O2 production, is limited by its preparation process and mainly produces low-purity industrial-grade H2O2, resulting in a severe shortage of domestic electronic-grade H2O2 production capacity. High-end H2O2 products are subject to import monopolies, keeping prices high. A one-step catalytic method using hydrogen and oxygen as raw materials is an ideal process for synthesizing electronic-grade H2O2. However, due to the safety hazards associated with direct hydrogen-oxygen mixing, traditional heterogeneous catalytic systems have long lacked technological breakthroughs. Palladium membrane reactors, with their unique structural features, allow H2 and O2 to be introduced into the reaction system from opposite sides of the membrane, and utilize the active hydrogen atoms at the low-pressure side membrane interface to directly react with oxygen to obtain the target product H2O2. This reduces the activation energy of the reaction while avoiding the risk of combustion and explosion caused by direct hydrogen-oxygen mixing. However, this system suffers from problems such as hydrogen embrittlement and cracking of the palladium membrane after low-temperature hydrogen dissolution, and the easy hydrogenation and decomposition of H2O2 on the palladium membrane surface. Therefore, in-depth research on the design and reaction mechanism of high-efficiency composite membrane materials will break through the key technical bottlenecks of insufficient material stability and product selectivity. Summary of the Invention
[0003] The purpose of this invention is to overcome the problems existing in the prior art and provide a silver-containing composite membrane including a titanium-silicon molecular sieve layer, its preparation method, and its application in the synthesis of hydrogen peroxide.
[0004] To achieve the above objectives, a first aspect of the present invention provides a silver-containing composite membrane comprising a titanium-silicon molecular sieve layer. The composite membrane comprises a composite palladium-based alloy material and a titanium-silicon molecular sieve attached to the surface of the composite palladium-based alloy material. The composite palladium-based alloy material contains Pd and Ag, and the molar ratio of Pd to Ag is 100:(25-100). The crystal structure of the composite palladium-based alloy material is face-centered cubic close-packed, and the lattice parameter k is 0.3998-0.4275 nm.
[0005] A second aspect of the present invention provides a method for preparing a silver-containing composite membrane comprising a titanium-silicon molecular sieve layer, the method comprising:
[0006] (1) Pd and Ag are deposited on the support, and then the support with Pd and Ag deposited is alloyed, wherein the molar ratio of Pd to Ag is 100:(25-100).
[0007] The alloying treatment is carried out as follows: after treatment in an activating atmosphere at a temperature of 520-550℃ and a pressure of 0.25-0.38MPa for 5-7 hours, the temperature is reduced to 150-200℃ at a rate of 40-70℃ / min. The gas providing the activating atmosphere includes H2 and Ar, and the volume ratio of H2 to Ar is 1:(0.8-6).
[0008] (2) The alloyed material is placed in a solution of a precursor containing titanium-silicon molecular sieve and subjected to hydrothermal crystallization, drying and calcination in sequence to obtain a composite membrane.
[0009] A third aspect of the present invention provides a composite membrane prepared by the method described above.
[0010] The fourth aspect of the present invention provides a composite palladium-based alloy material, which is the composite palladium-based alloy material defined above or the product of the alloying treatment described above.
[0011] The fifth aspect of this invention provides the application of the composite membrane described above in the synthesis of hydrogen peroxide.
[0012] Through the above technical solution, this invention prepares a composite palladium-based alloy material with a face-centered cubic close-packed crystal structure using electroplating, and synthesizes titanium-silicon molecular sieves on the surface of the composite palladium-based alloy material using an in-situ hydrothermal method. On the one hand, this allows hydrogen and oxygen to be introduced into the reaction system from opposite sides of the membrane, achieving physical isolation between the combustible gas (H2) and the combustion accelerant (O2), ensuring the safety of the reaction. On the other hand, it enables the efficient synthesis of H2O2 at the composite membrane interface, greatly improving the H2O2 generation rate and purity, yielding high-quality electronic-grade H2O2, and reducing the pressure of subsequent product separation and purification. This invention does not require any external energy source; it uses the composite membrane material as a catalyst to directly synthesize H2O2 from hydrogen and oxygen, offering advantages such as a simple process, clean and environmentally friendly operation, long service life, and low energy consumption. Simultaneously, the composite membrane of this invention solves the problems of palladium membranes being prone to hydrogen embrittlement and cracking at low temperatures, resulting in reduced mechanical strength, and the problem of H2O2 easily decomposing on the palladium membrane surface, causing reduced H2O2 selectivity. Attached Figure Description
[0013] Figure 1 This is a schematic diagram of the direct production of hydrogen peroxide from hydrogen and oxygen catalyzed by a palladium-silver-titanium-silicon molecular sieve composite membrane.
[0014] Figure 2 The results are X-ray diffraction (XRD) characterization of TS-2 molecular sieves stripped from the palladium film.
[0015] Figure 3 The results are the Fourier Transform Infrared (FTIR) spectra of the TS-2 molecular sieve stripped from the palladium film.
[0016] Figure 4 The results are UV-Vis characterization of TS-2 molecular sieves stripped from the palladium film.
[0017] Figure 5 These are scanning electron microscope (SEM) images of the palladium-based alloy film before (a) and after (b) loading TS-2 molecular sieve. Detailed Implementation
[0018] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0019] The first aspect of the present invention provides a silver-containing composite membrane including a titanium-silicon molecular sieve layer. The composite membrane includes a composite palladium-based alloy material and a titanium-silicon molecular sieve attached to the surface of the composite palladium-based alloy material. The composite palladium-based alloy material contains Pd and Ag, and the molar ratio of Pd to Ag is 100:(25-100), more preferably 100:(45-57). The crystal structure of the composite palladium-based alloy material is face-centered cubic close-packed, and the lattice parameter k is 0.3998-0.4275 nm.
[0020] In this invention, "face-centered cubic close packing" means that the 14 atoms involved in a unit cell belong to 4 layers: with one vertex as layer A, the three face-centered atoms and three vertex atoms adjacent to it belong to layer B, the next 6 atoms belong to layer C, and there is another vertex opposite to the vertex of layer A, which is in the next cycle of layer A.
[0021] In this invention, "lattice parameter k" refers to the physical dimensions of a unit cell in a crystal lattice, representing a fundamental structural parameter of a crystalline material. The lattice parameter k represents the edge length of the unit cell, that is, the edge length of each parallelepiped unit, and it is directly related to the bonding energy between atoms. A unit cell in three-dimensional space generally has three lattice parameters, denoted by a, b, and c. Based on the morphological distribution of the Bravais lattice, in the cubic crystal structure (face-centered cubic close packing) involved in this invention, these three constants are all equal, and therefore can be represented by parameter k. Changes in k reflect changes in the composition, stress state, etc., within the crystal. The lattice parameter k can be determined using X-ray diffraction (XRD) or atomic force microscopy (AFM).
[0022] According to the present invention, preferably, the half-width at half-maximum (WHM) of at least one characteristic peak of 2θ in the range of 25°-90° in the XRD pattern of the composite palladium-based alloy material is less than or equal to 0.1424; more preferably, the half-width at half-maximum (WHM) of all characteristic peaks of 2θ in the range of 25°-90° in the XRD pattern of the composite palladium-based alloy material is less than or equal to 0.1424.
[0023] According to the present invention, preferably, in the XRD pattern of the composite palladium-based alloy material, the full width at half maximum (FWHM) of the characteristic peak at 2θ = 40° ± 1° (i.e., the characteristic peak of crystal plane (110)) is less than or equal to 0.0698 (e.g., 0.0698, 0.06, 0.0524, 0.05, 0.045, 0.04, 0.035, 0.03, 0.025, 0.02, 0.015, 0.01, and any two of the above points), more preferably 0.051-0.06, or the full width at half maximum (FWHM) of the characteristic peak at 2θ = 46° ± 1° (i.e., the characteristic peak of crystal plane (111)) is less than or equal to 0.0873 (e.g., 0.0873, 0.07, 0.06, ...). The range of 0.0524, 0.05, 0.045, 0.04, 0.035, 0.03, 0.025, 0.02, 0.015, 0.01, and any two of the above points), more preferably 0.068-0.075, or the full width at half maximum (FWHM) of the characteristic peak at 2θ = 69° ± 1° (i.e., the characteristic peak of crystal plane (220)) is less than or equal to 0.1047 (e.g., 0.1047, 0.09, 0.08, 0.07). The range of 0.06, 0.0524, 0.05, 0.045, 0.04, 0.035, 0.03, 0.025, 0.02, 0.015, 0.01, and any two of the above points), more preferably 0.07-0.086, or the full width at half maximum (FWHM) of the characteristic peak at 2θ = 83° ± 1° (i.e., the characteristic peak of crystal plane (311)) is less than or equal to 0.1396 (e.g., 0.1396, 0.13, 0.12, ...). The range of 0.11, 0.1, 0.09, 0.08, 0.07, 0.06, 0.0524, 0.05, 0.045, 0.04, 0.035, 0.03, 0.025, 0.02, 0.015, 0.01, and any two of the above points), more preferably 0.09-0.1, or the full width at half maximum (FWHM) of the characteristic peak at 2θ = 87° ± 1° (i.e., the characteristic peak of crystal plane (222)) is less than or equal to 0.1424 (e.g., 0.14, 0.1, 0.09, 0.08, 0.07, 0.06, 0.0524, 0.05, 0.045, 0.04, 0.035, ... The range is 0.03, 0.025, 0.02, 0.015, 0.01, and any two of the above points, preferably 0.1-0.11; the "half-peak width" is defined as the peak width at half the peak height, i.e., the half-height width. The half-height width is converted to radians according to the Debye-Scherrer formula (D = Kγ / Bcosθ), and the radian value characterizes the size of the half-peak width. When the composite palladium-based alloy material has no characteristic peak at the corresponding 2θ position, the half-peak width is considered to be 0.
[0024] According to the present invention, preferably, the thickness of the composite palladium-based alloy material is 0.5-30 μm, more preferably 5-15 μm, and even more preferably 7-9 μm.
[0025] According to the present invention, preferably, the composite membrane is a tubular membrane.
[0026] According to the present invention, preferably, the composite membrane further includes a support, the composite palladium-based alloy material is attached to the support, and the thickness of the support can be 0.1-20 mm, more preferably 2-5 mm.
[0027] According to the present invention, preferably, the titanium silicate molecular sieve is at least one of TS-1, TS-2, Ti-β molecular sieve, Ti-MCM-41, Ti-MCM-48, Ti-TUD and Ti-HMS.
[0028] According to the present invention, preferably, the thickness of the titanium-silicon molecular sieve is 5-80 μm, more preferably 20-45 μm, and even more preferably 20-28 μm.
[0029] According to the present invention, preferably, the silicon-to-titanium molar ratio of the titanium-silicon molecular sieve is (20-500):1, more preferably (40-200):1; preferably, the average particle size of the titanium-silicon molecular sieve is 80-350 nm, more preferably 100-200 nm, and even more preferably 110-170 nm; preferably, the average pore size of the titanium-silicon molecular sieve is 0.2-125 nm, more preferably 5-35 nm, and even more preferably 5-10 nm; preferably, the specific surface area of the titanium-silicon molecular sieve is 40-800 m². 2 / g, more preferably 100-600m 2 / g, further preferably 450-580m 2 / g; preferably, the crystallinity of the titanium-silicon molecular sieve is greater than or equal to 85%, more preferably 88-93%.
[0030] In a preferred embodiment, such as Figure 1As shown, the composite membrane includes a support 1, and a composite palladium-based alloy material 2 and a titanium-silicon molecular sieve 3 sequentially attached to the support 1. When the composite membrane of the present invention is used to prepare hydrogen peroxide from hydrogen and oxygen, hydrogen is introduced from the support 1 side, and oxygen is introduced from the titanium-silicon molecular sieve 3 side. The hydrogen permeates and diffuses through the composite palladium-based alloy material 2 and, under the activation effect of the composite palladium-based alloy material 2, is transformed into active hydrogen atoms, which accumulate at the interface between the composite palladium-based alloy material 2 and the titanium-silicon molecular sieve 3, and then react with oxygen to generate hydrogen peroxide. In this invention, oxygen is dissolved in a stabilizer, which is a mixed buffer solution containing sodium dihydrogen phosphate (NaH2PO4) and methanol. Preferably, the molar ratio of sodium dihydrogen phosphate to methanol in the mixed buffer solution is 1:0.1-0.6; more preferably, the pH of the mixed buffer solution is 5-6. The sodium dihydrogen phosphate can be provided by an aqueous solution of sodium dihydrogen phosphate with a concentration of 0.1-1 mol / L, and the methanol can be provided by analytical grade methanol with a purity of 99-99.99%. The stabilizer of the present invention can also dissolve hydrogen peroxide in the mixed buffer solution, thus preventing the decomposition of hydrogen peroxide.
[0031] A second aspect of the present invention provides a method for preparing a silver-containing composite membrane comprising a titanium-silicon molecular sieve layer, the method comprising:
[0032] (1) Pd and Ag are deposited on a support, and then the support with Pd and Ag deposited is alloyed, wherein the molar ratio of Pd to Ag is 100:(25-100), more preferably 100:(45-57).
[0033] The alloying treatment is performed as follows: after treatment in an activating atmosphere at a temperature of 520-550℃ and a pressure of 0.25-0.38MPa for 5-7 hours, the temperature is reduced to 150-200℃ at a rate of 40-70℃ / min. The activating atmosphere consists of H2 and Ar, and the volume ratio of H2 to Ar is 1:(0.8-6), for example, 1:0.8, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, more preferably 1:(1.3-3.5).
[0034] (2) The alloyed material is placed in a solution of a precursor containing titanium-silicon molecular sieve and subjected to hydrothermal crystallization, drying and calcination in sequence to obtain a composite membrane.
[0035] The present invention reduces the activation energy of hydrogen permeation of the membrane material by performing heat treatment at a specific temperature and then cooling it at a specific rate, thereby improving the hydrogen permeation efficiency and stability of the membrane material (the half-width of the characteristic peak is small).
[0036] According to the present invention, preferably, the total thickness of Pd and Ag deposited on the support is 0.5-30 μm, more preferably 5-15 μm, and even more preferably 7-9 μm.
[0037] According to the present invention, preferably, the thickness of the support is 0.1-20 mm, more preferably 2-5 mm. The support can be provided by materials commonly used in the art that can withstand the operating temperature of the present invention without affecting hydrogen permeability, that is, materials that do not deform or affect hydrogen permeability at the operating temperature of the present invention. While ensuring excellent hydrogen permeability, to obtain better mechanical and thermal stability and reduce the amount of palladium used (reducing costs), preferably, the support is a porous support, which can be selected from at least one of porous ceramics, porous glass, porous metals (such as porous stainless steel), porous quartz, and polymers, more preferably from at least one of porous ceramics, porous metals, and polymers. Generally, the porosity distribution of the support ranges from 15-75%, and the average pore size is 0.05-0.4 μm. To obtain a tubular membrane, the support is preferably a tubular support. The porous ceramic material can be γ-Al₂O₃, with a porosity distribution range of 25-66% and an average pore size of 0.12-0.40 μm. Porous stainless steel can be made of 316L (Fe) 69 Cr 17 Ni 12 Mo2 has a porosity ranging from 32% to 71% and an average pore size of 0.08 to 0.36 μm. The polymer material can be polyimide, with a porosity ranging from 15% to 37% and an average pore size of 0.05 to 0.22 μm. The "porosity range" and "average pore size" can both be determined using nitrogen physical adsorption.
[0038] According to the present invention, preferably, the precursor solution of the titanium-containing silicon molecular sieve contains a silicon source, a titanium source, a template agent, water, and optionally a surfactant.
[0039] According to the present invention, preferably, the molar ratio of the silicon source, titanium source, template agent, water and surfactant is 100:(0.2-5):(5-60):(25-4000):(0-18), and more preferably 100:(0.5-2.5):(25-50):(50-2500):(0.1-6).
[0040] According to the present invention, preferably, the amount of the titanium-silicon molecular sieve precursor solution used is 0.2-2 ml (e.g., 0.2 ml, 0.3 ml, 0.4 ml, 0.5 ml, 0.6 ml, 0.7 ml, 0.8 ml, 0.9 ml, 1 ml, 1.5 ml, 2 ml) relative to 1 g of alloyed material, more preferably 0.3-0.5 ml.
[0041] According to the present invention, the silicon source can be a substance commonly used in the art that can provide silicon. Preferably, the silicon source is at least one of silicate esters, silicates and silicon dioxide, and more preferably selected from at least one of tetrabutyl orthosilicate, tetraethyl orthosilicate, sodium silicate, potassium silicate, silica sol and water glass.
[0042] According to the present invention, the titanium source can be a substance commonly used in the art that can provide titanium. Preferably, the titanium source is at least one of titanate, titanium salt, titanium oxysulfate and titanium difluoride, and more preferably selected from at least one of tetrabutyl titanate, tetraethyl titanate, titanium tetrachloride, titanium isopropoxide, titanium sulfate, titanium oxysulfate and titanium difluoride.
[0043] According to the present invention, preferably, the template agent is at least one of tetraalkylammonium hydroxide, alkylamine and tetraalkylammonium halide, and more preferably selected from at least one of tetrabutylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, triethylamine, hexadecyltrimethylammonium bromide and isopropylamine.
[0044] According to the present invention, preferably, the surfactant is at least one of nonionic surfactants, and more preferably selected from at least one of Tween-20, Tween-21, Tween-40, Tween-60, Tween-80, Tween-85, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine, polyoxyethylene alkylamide, and polyethers.
[0045] According to the present invention, preferably, the hydrothermal crystallization method is to first perform aging and then crystallize, wherein the aging conditions include: aging temperature 70-90℃ and aging time 5-8h; and the crystallization conditions include: crystallization temperature 165-185℃ and crystallization time 24-48h.
[0046] The aging process of the present invention can be carried out under stirring conditions, preferably at a stirring rate of 700-850 rpm.
[0047] The crystallization of the present invention can be carried out under stirring conditions, preferably with an aging stirring rate of 10-20 rpm.
[0048] According to the present invention, preferably, the drying conditions include: a drying temperature of 30-50°C and a drying time of 18-24 hours.
[0049] According to the present invention, preferably, the calcination conditions include: calcination temperature of 550-650℃ and calcination time of 3-5h.
[0050] A third aspect of the present invention provides a composite membrane prepared by the method described above.
[0051] The fourth aspect of the present invention provides a composite palladium-based alloy material, which is the composite palladium-based alloy material defined above or the product of the alloying treatment described above.
[0052] The fifth aspect of this invention provides the application of the composite membrane described above in the synthesis of hydrogen peroxide.
[0053] The present invention will be described in detail below through examples. In the following examples and comparative examples, the inner surface of the support is sealed with polytetrafluoroethylene (PTFE) material, and molecular sieves are loaded on the outer surface of the support. The PTFE material is then peeled off before application or performance testing.
[0054] Examples B1-B4
[0055] (1) Using a porous stainless steel tube as the support (tubular, inner diameter: 10 mm, outer diameter: 13 mm; average pore size: 0.25 μm, porosity: 65%), the support was first soaked in anhydrous ethanol for 30 minutes to remove surface contaminants such as dust and grease. Then, the surface and inner side of the support were rinsed with deionized water and placed in warm water for vacuum cleaning to remove residual ethanol from the pores. Finally, it was placed in an oven and dried at 423 K for 4 hours. Pd and Ag were deposited on the support using electroplating according to Faraday's law. The atomic molar ratio M of Pd to Ag is shown in Table 1. The effective film area was 23 cm². 2 The electroplating conditions were as follows: using a conductive layer carrier as the working electrode, a platinum electrode (Pd plated) and a silver electrode (Ag plated) as the counter electrodes, and a saturated calomel electrode as the reference electrode, at a temperature of 30°C, the metal ions (Pd) in the plating bath... 2+ Ag +The concentration was 0.1 mol / L. Electroplating experiments were conducted using cyclic voltammetry, with a working voltage range of -0.60 V to -0.90 V, a scan rate of 0.0075 V / s, a scan period of 1000, and a sensitivity of 0.0001 A / V. Simultaneously, during the electroplating process, a plunger-type constant flow pump was used to add the following solutions to the plating bath at rates of 1-2 ml / min: 0.05 mol / L ammonium palladium chloride ((NH4)2PdCl4) solution; 0.10 mol / L silver nitrate (AgNO3) solution; 0.12 ml / min: ethylenediamine (EDA, 99%, analytical grade); 0.05 ml / min: disodium ethylenediaminetetraacetate (EDTA-2Na, 99%, analytical grade); and 0.01 ml / min: bipyridine (C...). 10 H8N2 (99%, analytical grade). While adding the above solution, the plating bath was vigorously stirred (800-1000 r / min). Every 30 min of electroplating, the working electrode, cleaned with distilled water, was immersed for 10 min in 0.05 mol / L phosphoric acid (H3PO4) solution and 0.05 mol / L dipotassium hydrogen phosphate (K2HPO4) solution, respectively. After the cyclic voltammetry procedure, the working electrode was treated in distilled water at 80-100℃ for 15 min before being removed. The Pd and Ag deposited support was subjected to high-temperature alloying treatment. The alloying treatment method was as follows: after treatment in an activating atmosphere at temperature T1 and pressure P for a period of time (t); the temperature was then reduced to T2 at a cooling rate V. The activating atmosphere consisted of H2 and Ar, with the volume ratio of H2 to Ar equal to R1. The amount of activating atmosphere gas provided ensured that the alloying pressure was P. See Table 1 for details of the parameters.
[0056] (2) The composite palladium-based alloy material obtained in step (1) was placed in the precursor of TS-2 molecular sieve for hydrothermal crystallization (aging and crystallization were performed sequentially), drying and calcination. The molar ratio R2 of silicon source, titanium source, template agent, water and nonionic surfactant and the conditions of each step are shown in Table 1 to obtain the composite membrane precursor. In the TS-2 molecular sieve precursor solution, tetrabutylammonium hydroxide (TBAOH) was used as the template agent, tetrabutyl orthosilicate (TEOS) was used as the silicon source, tetrabutyl titanate (TBOT) was used as the titanium source and Tween-20 was used as the nonionic surfactant. The amount of titanium-silicon molecular sieve precursor solution used was 0.4 ml per 1 g of alloyed material.
[0057] Table 1
[0058]
[0059] Example B5
[0060] The procedure was carried out in accordance with Example B1, except that the molar ratio of Pd to Ag was changed to 100:67.
[0061] Example B6
[0062] The procedure was carried out in accordance with Example B1, except that the molar ratio of Pd to Ag was changed to 100:25.
[0063] Example B7
[0064] The procedure was carried out in accordance with Example B1, except that the molar ratio of Pd to Ag was changed to 100:100.
[0065] Comparative Example BD1
[0066] The procedure was carried out in accordance with Example B1, except that the temperature was reduced to T2 at a rate of V = 35°C / min.
[0067] Comparative Example BD2
[0068] The process was carried out in accordance with Example B1, except that the alloying temperature T1 = 480°C.
[0069] Comparative Example BD3
[0070] The process was carried out in accordance with Example B1, except that the alloying pressure P = 0.18 MPa.
[0071] Test case
[0072] (I) The materials obtained after alloying treatment in step (1) of each embodiment and comparative example (i.e., composite palladium-based alloy materials) were characterized. The characterization method is as follows, and the crystal structure parameters of the composite palladium-based alloy materials are shown in Table 2.
[0073] The crystal structure analysis of the composite palladium-based alloy was performed on an X'Pert PRO / PANalytical automated X-ray diffractometer manufactured by Philips, Netherlands. The experimental conditions were Cu K α X-rays (λ = 0.1543 nm), tube voltage 40 kV, current 40 mA, diffraction angle 2θ scan range 10-90°. The interplanar spacing of the sample was calculated using the Bragg equation.
[0074] d=λ / 2sinθ
[0075] Where λ corresponds to Cu K α The wavelength of the radiation, θ is the angle of the diffraction peak.
[0076] The crystal structure of the composite palladium-based alloy was tested at the European Synchrotron Radiation Facility (beam BM25A) in France, which has higher resolution, with synchrotron radiation λ = 0.0618886 nm or 0.077449 nm and tube voltage of 10.0335 keV or 20.0335 keV. Initially, a 10 × 1 mm sample was used. 2 The sample was placed in a 2mm diameter quartz capillary tube, with both ends sealed with quartz wool. The capillary tube was then mounted on a rotating sample stage (to ensure uniform temperature and a larger X-ray irradiation area). The test temperature range was 298-473K (heated by a hot air blower), and the pressure range was 10... -4 The test atmosphere was -130 kPa. Hydrogen gas was first introduced and treated for 30 minutes, then a vacuum was drawn, and helium gas was introduced as a protective gas for measurement.
[0077] Methods for testing the lattice parameters of composite palladium-based alloy materials: Combining the above-mentioned in-situ XRD tests, the cell parameters of the palladium-based alloy materials are obtained (represented by three cell constants a, b, and c, and the three inter-edge angles α, β, and γ). According to the formula d1 = a / (α... 2 +β 2 +γ 2 ) 0.5 d2=b / (α) 2 +β 2 +γ 2 ) 0.5 d3=c / (α) 2 +β 2 +γ 2 ) 0.5 The interplanar spacing (d1 d2 d3) of the corresponding characteristic crystal planes is calculated. That is, the PdAg alloy material obtained in this invention belongs to the face-centered cubic close-packed (FCC) structure, and its characteristic crystal planes include (110), (111), (220), (311), (222). At the same time, according to the X-ray diffraction results, a series of different characteristic crystal plane ratios (the intensity corresponding to different crystal planes) can be obtained. For example, in the PdAg alloy material obtained in this invention, the (110) plane corresponds to the characteristic peak at 2θ = 40° ± 1°, the (111) plane corresponds to the characteristic peak at 2θ = 46° ± 1°, the (220) plane corresponds to the characteristic peak at 2θ = 69° ± 1°, the (311) plane corresponds to the characteristic peak at 2θ = 83° ± 1°, and the (222) plane corresponds to the characteristic peak at 2θ = 87° ± 1°. Using HighScorePlus analysis software, combined with the peak intensities of the aforementioned characteristic crystal planes, the lattice parameters k of the corresponding materials are calculated.
[0078] The thickness of the composite palladium-based alloy material was tested by scanning electron microscopy (model: JSM-7610F). The thickness of the alloy film was determined by measuring the corresponding scale according to the magnification. The surface smoothness of the obtained composite palladium-based alloy material could also be observed by scanning electron microscopy. The results showed that the surface of the composite palladium-based alloy material prepared by this invention was smooth and free of defects.
[0079] The method for testing the half-peak width (WHM) of composite palladium-based alloy materials is as follows: based on the XRD spectrum test results, combined with HighScore Plus software analysis, the radian value of the WHM is obtained.
[0080] (II) Solid-phase exfoliation treatment was performed on the composite membranes obtained from each embodiment and comparative example to remove the molecular sieve for characterization. The characterization method is as follows, and the relevant structural parameters of the titanium-silicon molecular sieve attached to the surface of the composite palladium-based alloy material are obtained, as shown in Table 2.
[0081] Titanium silicate molecular sieve samples were analyzed using an Empyrean X-ray diffractometer from Malvern-Panalytical. The testing conditions were: Cu target, Ka radiation, Ni filter, tube voltage 40 kV, tube current 40 mA, scintillation counter, step size 0.0131°, scan range 5–35°, and scan rate 2.5° / min. The results showed that it is a TS-2 molecular sieve with a double ten-membered ring cross-channel structure (MFI structure). Figure 2 The XRD pattern of the molecular sieve obtained in Example B1 is shown. The five characteristic peaks between 23° and 25° indicate that the material contains a double ten-membered ring cross-channel structure, consistent with the characteristics of titanium-silicon molecular sieves. The XRD patterns of the molecular sieves in each example are... Figure 2 Similarly, this indicates that the obtained molecular sieves are all TS-2 titanium-silicon molecular sieves;
[0082] The specific surface area of titanium-silicon molecular sieves was determined using a Micromeritics ASAP 2020 physical adsorption instrument. Samples were subjected to high vacuum treatment at 363 K and 573 K for 1 h and 3 h, respectively, followed by adsorption at a constant temperature of 77 K using N2 as the adsorbate. The BET specific surface area was obtained from the N2 adsorption isotherm combined with the BET equation; the pore distribution was determined using the BJH method, calculated from the desorption branch of the N2 adsorption isotherm.
[0083] Test method for crystallinity of titanium-silicon molecular sieves: A conventional X-ray diffractometer was used with a tube voltage of 40 kV, a tube current of 40 mA, and a scanning speed of 2.5° / min. The diffraction patterns of the samples were recorded within the range of 2θ = 5–35°. A titanium-silicon molecular sieve sample of grade T302641 from Shanghai Aladdin Biochemical Technology Co., Ltd. was used as a reference sample, with its relative crystallinity set to 100. The relative crystallinity of each sample was calculated by summing the peak intensities of its characteristic diffraction peaks at 2θ = 22.319°, 22.549°, 23.083°, 23.580°, 24.299°, 25.208°, 25.577°, and 28.401° and comparing this sum with the sum of the peak intensities of the reference sample.
[0084] The methods for testing the average particle size of titanium-silicon molecular sieves are as follows: observe the microstructure of the molecular sieve in the sample using a transmission electron microscope and measure the diameter according to the scale bar; calculate the corresponding particle size distribution by taking the average of several samples using mathematical statistical methods.
[0085] The stretching vibration characteristic peaks of the Si-O-Ti framework structure of the titanium-silicon molecular sieve were measured on a Bruker INVENIO R and Tensor 27 infrared spectrometer with KBr as the background matrix material and after pressing the doped titanium-silicon molecular sieve into a pellet. (The infrared spectral characterization results of the molecular sieve obtained in Example B1 are shown in the figure.) Figure 3 As shown, 968cm -1 and 1213cm -1 The wavenumber characteristic peaks satisfy the stretching vibrations of the Si-O-Ti framework structure, exhibiting the framework characteristics of titanium-silicon molecular sieves. The characterization results of the stretching vibration characteristic peaks of the Si-O-Ti framework structure of the titanium-silicon molecular sieves in each embodiment are consistent with... Figure 3 similar.
[0086] The Ti elemental chemical environment of the titanium-silicon molecular sieve was measured using an Agilent Cary 5000UV-Vis-NIR spectrometer to determine whether it was a four-coordinate framework titanium structure (the UV spectral characterization results of the molecular sieve obtained in Example B1 are shown below). Figure 4 As shown, the characteristic peak at a wavelength of 206 nm satisfies the requirements of framework titanium Ti. 4+ The characteristic structure of the four-coordinate system exhibits the framework structure of a titanium-silicon molecular sieve. The Ti elemental chemical environment characterization results of the titanium-silicon molecular sieves in each embodiment are consistent with... Figure 4 similar.
[0087] The thickness of the titanium-silicon molecular sieve was determined by scanning electron microscopy (SEM) and measured according to the corresponding scale at the magnification. Figure 5 (a) is a scanning electron microscope (SEM) image of the composite palladium-based alloy material before loading with titanium-silicon molecular sieves, and (b) is a scanning electron microscope (SEM) image of the composite palladium-based alloy material after loading with titanium-silicon molecular sieves.
[0088] (III) Overall testing of composite membranes
[0089] E act (Hydrogen permeation activation energy, unit: kJ·mol) -1 The test method involves measuring the hydrogen permeation rate from 573 K to 773 K under a pressure difference of 0.1 MPa, combined with the Arrhenius equation J. H2 =J H2 ° exp(- E act / RT), calculated through measurement, where J H2 It is the hydrogen permeation diffusion rate, J H2 ° is the hydrogen permeation diffusion coefficient, and R is the gas constant. The higher the hydrogen permeation activation energy, the higher the hydrogen mass transfer resistance of the composite membrane material, and the more difficult it is for hydrogen to permeate and diffuse through the composite membrane.
[0090] J H2 (Hydrogen permeation diffusion rate, unit: mol·m) -2 ·s -1 The test method involves measuring the volume of hydrogen passing through the palladium-based composite membrane per minute (in liters) at 20℃ and a pressure difference of 0.1 MPa, and then normalizing it to the hydrogen permeation rate (mol·m²) based on the membrane area (square meters). -2 ·s -1 ).
[0091] J N2 (Nitrogen permeation diffusion rate, unit: mmol·m) -2 ·s -1 The test method involves measuring the volume (mL) of nitrogen gas passing through the palladium-based composite membrane per minute at 20℃ and a pressure difference of 0.1 MPa, then normalizing this volume to the hydrogen permeation rate (mmol·m²) based on the membrane area (m²). -2 ·s -1 ).
[0092] The elemental composition of the composite film was analyzed by X-ray fluorescence (XRF) combined with inductively coupled plasma optical emission spectroscopy (ICP-OES), and the valence states of the elements were determined by X-ray photoelectron spectroscopy (XPS).
[0093] Table 2
[0094]
[0095]
[0096] (IV) Application Testing
[0097] The performance of the composite membranes prepared in the above embodiments and comparative examples in the preparation of hydrogen peroxide was tested.
[0098] The composite membrane prepared above was encapsulated in a tubular reactor. Nitrogen gas was first introduced at a flow rate of 10 mL / min to raise the temperature to 473 K, activating the composite membrane for 2 hours. O2 was introduced into the reactor from the outside of the composite membrane, and H2 from the inside. Through dissolution and diffusion, the H2 permeates through the palladium membrane to the outer palladium membrane interface and undergoes an oxidation reaction with oxygen dissolved in a mixed buffer solution (the molar ratio of sodium dihydrogen phosphate to methanol in the mixed buffer solution was 1:0.35, the pH of the mixed buffer solution was 5.5, the sodium dihydrogen phosphate was provided by an aqueous solution with a concentration of 0.1 mol / L, and the methanol was provided by analytical grade methanol with a purity of 99.5%). The reaction temperature was controlled at 353 K, the transmembrane pressure difference was 0.3 MPa, and the volumetric flow rate ratio of H2:O2:N2 (N2 was a dilution gas, mixed with oxygen) was 21:25:30 mL / min. During the reaction, real-time monitoring (analysis of gaseous components such as hydrogen and oxygen using an Agilent 7890B gas chromatograph equipped with a TCD detector) was conducted to analyze the content and proportion of hydrogen, oxygen, and nitrogen in the tail gas, thereby calculating the feed conversion rate. The H2O2 formation rate was measured using a potentiometric titrator (Mettler-Toledo T90 fully automated potentiometric titrator), and the hydrogen peroxide selectivity was analyzed using iodometric titration. Based on the detection results, the hydrogen conversion rate and hydrogen peroxide selectivity were calculated. The product was tested every 5 hours. The continuous operating time was recorded when the hydrogen conversion rate or hydrogen peroxide selectivity decreased to 90% of the initial value. The initial reaction values and experimental measurements after reaching the continuous operating time are shown in Table 3. The calculation formulas for hydrogen conversion rate, hydrogen peroxide selectivity, hydrogen utilization rate, and hydrogen-nitrogen selectivity are as follows:
[0099] Hydrogen conversion rate (C) H2 = (Amount of hydrogen gas introduced into the reactor - Amount of hydrogen gas at the reactor outlet) / Amount of hydrogen gas introduced into the reactor
[0100] Hydrogen peroxide selectivity (S H2O2 = (Hydrogen peroxide concentration in buffer solution * buffer solution volume) / (Amount of hydrogen gas introduced into the reactor - Amount of hydrogen gas discharged from the reactor)
[0101] Hydrogen utilization rate (Y) H2 = (Hydrogen peroxide concentration in buffer solution * buffer solution volume) / Amount of hydrogen gas introduced into the reactor
[0102] Hydrogen-nitrogen selectivity (α(H2 / N2)) refers to the ratio between the hydrogen permeation / diffusion rate and the nitrogen permeation / diffusion rate at the defect site on the palladium film. A higher value indicates higher mechanical structural stability of the palladium film and fewer defects in the composite film material. Specifically, this is determined by measuring the hydrogen permeation / diffusion rate (J / N2) of the palladium film. H2The nitrogen permeation diffusion rate at the defect under the same conditions (353 K, 0.3 MPa transmembrane pressure difference) (J) N2 According to the formula α(H2 / N2)=J H2 / J N2 The above measurement methods were used to obtain the result.
[0103] Table 3
[0104]
[0105] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A silver-containing composite membrane comprising a titanium-silicon molecular sieve layer, characterized in that, The composite membrane comprises a composite palladium-based alloy material and a titanium-silicon molecular sieve attached to the surface of the composite palladium-based alloy material. The composite palladium-based alloy material is composed of Pd and Ag, with a molar ratio of Pd to Ag of 100:(25-100). The composite palladium-based alloy material has a face-centered cubic close-packed crystal structure with a lattice parameter k of 0.3998-0.4275 nm. In the XRD pattern of the composite palladium-based alloy material, 2θ = 40 nm. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.0698, and 2θ = 46. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.0873, and 2θ = 69. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.1047, and 2θ = 83. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.1396, and 2θ = 87. o ±1 o The full width at half maximum (FWHM) of the characteristic peak at that location is less than or equal to 0.1424. The crystal phase structure analysis of the composite palladium-based alloy material was performed using an X-ray diffractometer. The experimental conditions were Cu... K α ray, λ = 0.1543 nm, tube voltage 40 kV, current 40 mA, diffraction angle 2 θ The scanning range is 10-90. o ; The method for testing the half-peak width (WHM) of composite palladium-based alloy materials is as follows: based on the X-ray diffraction test results, combined with HighScore Plus software analysis, the radian value of the WHM is obtained.
2. The composite membrane according to claim 1, wherein, The thickness of the composite palladium-based alloy material is 0.5-30µm.
3. The composite membrane according to claim 1, wherein, The thickness of the composite palladium-based alloy material is 5-15µm.
4. The composite membrane according to claim 1, wherein, The titanium-silicon molecular sieve is at least one of TS-1, TS-2, Ti-β molecular sieve, Ti-MCM-41, Ti-MCM-48, Ti-TUD and Ti-HMS; And / or, the thickness of the titanium silicate molecular sieve is 5-80µm; And / or, the silicon-to-titanium molar ratio of the titanium-silicon molecular sieve is (20-500):1; the average particle size is 80-350 nm; the average pore size is 0.2-125 nm; and the specific surface area is 40-800 m². 2 / g; crystallinity greater than or equal to 85%.
5. The composite membrane according to claim 1, wherein, The thickness of the titanium-silicon molecular sieve is 20-45µm.
6. The composite membrane according to claim 1, wherein, The silicon-to-titanium molar ratio of titanium-silicon molecular sieves is (40-200):1; the average particle size is 100-200 nm; the average pore size is 5-35 nm; and the specific surface area is 100-600 m². 2 / g; crystallinity is 88-93%.
7. The composite membrane according to claim 1, wherein, The composite membrane is a tubular membrane; And / or, the composite membrane further includes a support, on which the composite palladium-based alloy material is attached, and the thickness of the support is 0.1-20 mm.
8. The composite membrane according to claim 7, wherein, The thickness of the support is 2-5mm.
9. A method for preparing a silver-containing composite membrane including a titanium-silicon molecular sieve layer, characterized in that, The method includes: (1) Pd and Ag are deposited on the support, and then the support with Pd and Ag deposited is alloyed, wherein the molar ratio of Pd to Ag is 100:(25-100). The alloying treatment is carried out as follows: after treatment in an activating atmosphere at a temperature of 520-550℃ and a pressure of 0.25-0.38MPa for 5-7 hours, the temperature is reduced to 150-200℃ at a rate of 40-70℃ / min. The gas providing the activating atmosphere includes H2 and Ar, and the volume ratio of H2 to Ar is 1:(0.8-6). (2) The alloyed material is placed in a solution of titanium-silicon molecular sieve precursor and subjected to hydrothermal crystallization, drying and calcination in sequence to obtain a composite membrane.
10. The method according to claim 9, wherein, The total thickness of Pd and Ag deposited on the support is 0.5-30µm; And / or, the thickness of the support is 0.1-20 mm.
11. The method according to claim 9, wherein, The total thickness of Pd and Ag deposited on the support is 5-15µm; And / or, the thickness of the support is 2-5 mm.
12. The method according to claim 9, wherein, The precursor solution of the titanium-containing silicon molecular sieve contains a silicon source, a titanium source, a template agent, water, and an optional surfactant.
13. The method according to claim 12, wherein, The molar ratio of the silicon source, titanium source, template agent, water and surfactant is 100:(0.2-5):(5-60):(25-4000):(0-18); And / or, relative to 1g of alloyed material, the amount of the titanium-silicon molecular sieve precursor solution used is 0.2-2ml; And / or, the silicon source is at least one of silicate ester, silicate and silicon dioxide; And / or, the titanium source is at least one of titanate, titanium salt, titanium oxysulfate and titanium difluoride; And / or, the template agent is at least one selected from tetraalkylammonium hydroxide, alkylamine, and tetraalkylammonium halide; And / or, the surfactant is at least one of nonionic surfactants.
14. The method according to claim 12, wherein, The molar ratio of the silicon source, titanium source, template agent, water and surfactant is 100:(0.5-2.5):(25-50):(50-2500):(0.1-6).
15. The method according to claim 12, wherein, The silicon source is selected from at least one of tetrabutyl orthosilicate, tetraethyl orthosilicate, sodium silicate, potassium silicate, silica sol, and water glass.
16. The method according to claim 12, wherein, The titanium source is selected from at least one of tetrabutyl titanate, tetraethyl titanate, titanium tetrachloride, titanium isopropoxide, titanium sulfate, titanium oxysulfate, and titanium difluoride.
17. The method according to claim 12, wherein, The template agent is selected from at least one of tetrabutylammonium hydroxide, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, triethylamine, hexadecyltrimethylammonium bromide, and isopropylamine.
18. The method according to claim 12, wherein, The surfactant is selected from at least one of Tween-20, Tween-21, Tween-40, Tween-60, Tween-80, Tween-85, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine, polyoxyethylene alkylamide, and polyethers.
19. The method according to claim 9, wherein, The hydrothermal crystallization method involves aging followed by crystallization. The aging conditions include an aging temperature of 70-90℃ and an aging time of 5-8 hours. The crystallization conditions include a crystallization temperature of 165-185℃ and a crystallization time of 24-48 hours. And / or, the drying conditions include: drying temperature 30-50℃, drying time 18-24h; And / or, the calcination conditions include: calcination temperature of 550-650℃ and calcination time of 3-5h.
20. The composite membrane prepared by the method according to any one of claims 9-19.
21. A composite palladium-based alloy material, characterized in that, The composite palladium-based alloy material is the composite palladium-based alloy material in the silver-containing composite film as defined in any one of claims 1-8 or the product of the alloying treatment in step (1) of the method described in any one of claims 9-11.
22. The use of the composite membrane according to any one of claims 1-8 or 20 in the synthesis of hydrogen peroxide.
Citation Information
Patent Citations
Palladium-copper composite membrane material loaded with TS-1 molecular sieve and preparation and application of composite membrane material
CN109876745A
Method for carrying out gas-phase propylene epoxidation reaction in palladium membrane reactor
CN110903265A